1997
DOI: 10.1089/hum.1997.8.3-275
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Site-Specific Integration of the Recombinant Adeno-Associated Virus 2 Genomes in Human Cells

Abstract: The adeno-associated virus 2 (AAV)-based vector system has been suggested for its potential use in human gene therapy because the wild-type (wt) AAV genome appears to integrate into the human chromosomal DNA in a site-specific manner. We systematically investigated the integration patterns of the recombinant AAV genomes lacking one or both the viral coding sequences. Four recombinant AAV genomes were constructed containing the genes for resistance to tetracycline (TcR) and the herpesvirus thymidine kinase (TK)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(57 citation statements)
references
References 44 publications
2
55
0
Order By: Relevance
“…Southern blot, dot blot, and progeny inheritance tests, however, strongly indicated that several copies of transgenes flanked by AAV-ITRs were randomly integrated into the zebrafish genome at a single locus and that this construct was stably transmitted. The integration pattern of transgenes flanked by AAV-ITRs is consistent with the random integration of recombinant AAV in vitro in the absence of Rep and Cap proteins (Ponnazhagan et al, 1997;Miao et al, 1998).…”
Section: Integration Pattern Of Transgenes Flanked By Aav-itrssupporting
confidence: 69%
“…Southern blot, dot blot, and progeny inheritance tests, however, strongly indicated that several copies of transgenes flanked by AAV-ITRs were randomly integrated into the zebrafish genome at a single locus and that this construct was stably transmitted. The integration pattern of transgenes flanked by AAV-ITRs is consistent with the random integration of recombinant AAV in vitro in the absence of Rep and Cap proteins (Ponnazhagan et al, 1997;Miao et al, 1998).…”
Section: Integration Pattern Of Transgenes Flanked By Aav-itrssupporting
confidence: 69%
“…Although the wild-type virus efficiently integrates in a specific location in the human genome (AAVS1 on chromosome 19), 29 integration of rAAV genomes is typically passive, of low frequency and largely random. [30][31][32] The vast majority of rAAV vector genomes remain as episomes in the host cell nucleus, with only an estimated 0.5% of genomes integrating into the host genome, 33 probably at pre-existing chromosomal breaks. 34 However, as doses ranging from 10 11 to 10 12 virus particles may be administered to the human eye, 15,35 this small fraction of integrating vector genomes potentially equates to a substantial number of integration events.…”
Section: Introductionmentioning
confidence: 99%
“…14 However, rAAV is limited by the size of DNA that can be packaged to between 3.5 kb and 5 kb and, unlike wild-type AAV, rAAV integrates randomly in the host chromosomes. 15 X-linked hyper IgM (X-HIM) is a primary immune deficiency disease that results from defects in the gene for CD40 ligand. 16 CD40 ligand is a 39 kDa glycoprotein expressed transiently on the surface of activated CD4 + T cells 17 and delivers contact-dependent help to B cells and monocytes.…”
Section: Introductionmentioning
confidence: 99%